The Erosion–Corrosion Behavior of Eutectic High Chromium Cast Irons Reinforced by TiC Particles - Tian-Quan Tu; Shen-Lin Liu; Kai-Hong Zheng; Boris B. Khina; Artur I. Pokrovsky; Zhi-Chao Luo (Metals, 2022)
In this work, high chromium cast irons (HCCIs) reinforced by TiC particles are designed and fabricated to improve the erosion–corrosion and wear resistances of materials for the pumping and handling applications. The TiC particles are formed by the in situ solidification method. The experimental results show that the hardness of as-cast HCCIs is improved significantly with TiC volume fraction. It can be as high as 63 HRC when the TiC volume fraction is 9.8%. The introduction of TiC increases the abrasive wear resistance of the HCCIs in both as-cast and heat-treated states. However, it is unexpected to find that the presence of TiC significantly reduces the erosion–corrosion performance. It suggests that corrosion-enhanced erosion is the dominant mechanism that controls the mass loss of the TiC-strengthened HCCIs.